IMPACT OF EXTERNAL DEBT ON FINANCIAL DEVELOPMENT: AN EMPIRICAL ANALYSIS OF SELECTED EAST ASIAN AND PACIFIC COUNTRIES - Nguyen, Hoang Minh (Trường Đại học Đà Lạt, 2024)
This article explores the impact of external debt on financial development in a group of fifteen selected East Asian and Pacific countries from 1992 to 2021. These countries include Cambodia, China, Fiji, Indonesia, Lao PDR, Mongolia, Myanmar, Papua New Guinea, the Philippines, Samoa, the Solomon Islands, Thailand, Tonga, Vanuatu, and Vietnam. Data were extracted from the World Bank and International Monetary Fund databases. This study employs random effects and fixed effects models, Driscoll-Kraay standard errors, and the generalized method of moments to test two hypotheses. The results indicate that external debt has a positive impact on the financial development of these East Asian and Pacific countries, where economic growth plays a vital role in promoting financial development. Additionally, a nonlinear impact of external debt on the financial development of these East Asian and Pacific countries is observed. Based on these findings, it is recommended that appropriate financial development policies be implemented in the identified countries.